SINERGITAS PERAN PONDOK PESANTREN DALAM PENINGKATKAN INDEK PEMBANGUNAN MANUSIA (IPM) DI INDONESIA - Suib, M Syaiful (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2017)
The concept of this study examines the Synergy of Pondok Pesantren's Role on the Improvement of Human Development Index (IPM) in Indonesia. Calculation of HDI standard include life expectancy, education level and standard of living of a region is in accordance with national standardization. This research is a qualitative research to collect data relating to the construction of conceptual thinking of the researcher is how the components, ways to overcome and what strategy will be done by PP to increase HDI in certain area that become its territory. Based on the data obtained the level of HDI in Indonesia is still low, this is due to the community's response to development is still not maximal, therefore the Government to further increase the HDI in the region, it is necessary cooperation with Pondok pesantren. Surely the role of this PP will have a positive impact on the increase of HDI in the region and become a reference for the stakeholders to utilize and increase the HDI in the region through boarding school. Broadly speaking, HDI will increase if education, health and other areas, there is a response from the community and contribute to the community. This opportunity will provide added value to the increase of HDI through the role of Pondok Pesantren.